INCREASING THE EFFECTIVENESS OF GROUP SWIMMING LESSONS OF A SPORTS AND HEALTH-IMPROVING ORIENTATION - Stolyarova, E.P.; Nizhnik, G.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the effectiveness of various approaches to planning sports and recreational activities in swimming in subscription groups. Methods and structure of the study. To determine the effectiveness of planning classes in subscription swimming groups, testing of the motor and swimming readiness of those involved in primary school age 8-12 years old was used. Results and conclusions. Classes in subscription swimming groups, built on the basis of the stages of initial training, preliminary and basic training with an emphasis on increasing the length of the swim segments, at each stage showed an advantage over the traditional approach based on the program of swimming initial training groups with an emphasis on mastering the technique of methods swimming, and have a healthier effect. Those involved in the experimental group ultimately had a higher level of swimming fitness, endurance and strength abilities.